Vital Service Captivity: Coping Strategies and Identity Negotiation. (February 2022) - Guillemot, Samuel; Dyen, Margot; Tamaro, Annick
Nursing homes are the quintessential example of vital service captivity. Consumers need vital services when they can no longer fulfil their basic needs on their own and their only choice is to delegate them to the market (e.g. care services for long-term and chronic illnesses, eating assistance at mealtimes). The service is referred to as 'captive' because older people are generally unwilling to use it, and when they have to, their options are limited. For elderly consumers, there is 'no exit possible', and as such they must integrate the service into their sense of self. The paper aims to (1) identify strategies for coping with vital service captivity and (2) present the identity negotiation mechanisms that lead people to choose one strategy over another. The study was conducted over a 6-month period in three nursing homes. Data collection includes semi-structured interviews, focus groups, participant observations, and micro-interviews with consumers – elderly residents and their families – and nursing home staff. Its main contribution is to highlight that coping with vital service captivity is a differential process. Consumers implement multiple coping strategies simultaneously, and these strategies are linked to three areas: routinization, socialization, and assimilation of a new social status. Moreover, implementing coping strategies means striking a balance between 'disengagement' and 'engagement' that not only takes into account former life trajectory, future prospects, and social comparisons, but also any changes in physical or cognitive skills and family support. Understanding these coping strategies and identity negotiation mechanisms highlights some unintended consequences on residents' well-being, such as the importance of standardizing how the service is organized because it provides a stable framework, or the importance given to the well-being of all stakeholders (other consumers, staff) as a result of the community living situation.